Patrimonio cultural y turismo en San Pedro de Atacama, Chile (2013)
This article observes social dynamics and the impact tourism has over the community of San Pedro de Atacama, Chile. How is cultural patrimony constructed, appropriated and valued as a function of tourism? How is the landscape transformed and adapted to the dynamics of tourism? How does population modify the use and ways in which land and resources are recognized? How do visitors appropriate space? These are some of the questions that motivate this article.